Face Masks and Emotional Blindness: The Impact of Facial Occlusion on Emotion Recognition Among Indonesian Adolescents - Rizqi, Putri Umrotur; Yasin, Muhammad (Indonesian Scientific Publication, 2025)
The COVID-19 pandemic has transformed nonverbal communication by introducing face masks into daily interactions, particularly affecting adolescents during a critical phase of socioemotional development. This study investigates how face masks influence the accuracy and cognitive processing of basic facial emotion recognition among Indonesian adolescents. Employing a between-subjects experimental design, 200 adolescents aged 12–18 were randomly assigned to view masked or unmasked facial expressions depicting six basic emotions. Emotion recognition accuracy, reaction times, and confidence ratings were collected using the Labvanced platform. The results indicate that face masks significantly reduce the accuracy of emotion recognition, with the most pronounced impairments observed for disgust and fear. Reaction times were longer across all masked conditions, suggesting increased cognitive load. Anger and sadness, which are more discernible from the eye region, maintained relatively higher recognition rates. Adolescents employed compensatory strategies, such as focusing on the eye region and contextual cues, but these were insufficient to fully counteract the interpretive challenges introduced by masking. The findings have critical implications for adolescent mental health and educational environments. Impaired emotion recognition may contribute to social withdrawal, miscommunication, and emotional dysregulation, ultimately affecting academic performance and peer relationships. These challenges are further complicated by cultural norms in Indonesia that may discourage overt emotional expression. Prolonged mask-wearing may also disrupt the development of emotional intelligence and social cognition. Interventions that promote emotion literacy particularly those that address masked and ambiguous facial cues are recommended. Schools, parents, and policymakers should work collaboratively to support adolescents through targeted educational programs and culturally sensitive socioemotional training.